Prognostic Biomarkers for Pancreatic Ductal Adenocarcinoma: An Umbrella Review - Wang, Yizhi; Zhong, Xi; Zhou, Li; Lu, Jun; Jiang, Bolun; Liu, Chengxi; Guo, Junchao (Frontiers in Oncology, 2020)
Background：Pancreatic ductal adenocarcinoma (PDAC) leads to a majority of cancer-related death among cancers due to its morbidity with similar mortality. Lack of effective prognostic biomarkers is the main reason for the belated postoperative intervention of recurrence which causes high mortality. Numerous systematic reviews and meta-analyses have explored the prognostic value of biomarkers in PDAC so far. In this article, we performed an umbrella review analyzing these studies to provide an overview of associations between prognostic biomarkers and PDAC survival outcome and synthesize these results to guide better clinical practice. Methods: Systematic reviews and meta-analyses investigating the associations between PDAC survival outcomes and prognostic biomarkers were acquired via PubMed and Embase database from inception till 1 February, 2020. Associations supported by nominally statistically significant results were classified into strong, highly suggestive, suggestive and weak based on several critical factors such as the statistical significance of summary estimate, the number of events, the estimate of the largest study included, interstudy heterogeneity, small-study effects, 95% predictive interval (PI), excess significance bias, and the results of credibility ceiling sensitivity analyses. Results: We included 41 meta-analyses containing 63 associations between PDAC survival outcomes and prognostic biomarkers. Although, none was supported by strong evidence among these associations, association between C-reactive protein to albumin ratio (CAR) and PDAC overall survival (OS) and association between neutrophil-lymphocyte ratio (NLR) and PDAC OS were supported by highly suggestive evidence. Otherwise, the association between lactate dehydrogenase (LDH) and PDAC OS was supported by suggestive evidence. The remaining 60 associations were supported by weak or not suggestive evidence. Conclusion: Associations between CAR or NLR and PDAC OS were supported by highly suggestive evidence. And the association between LDH and PDAC OS was supported by suggestive evidence. Although the methodological quality of the included systematic reviews and meta-analyses which were evaluated by AMSTAR2.0 is generally poor, the identification of the relatively robust prognostic biomarkers of PDAC may guide better postoperative intervention and follow-up to prolong patients’ survival.